(untitled) (Swiss Medical Weekly, 2024)
INTRODUCTION: Entrustable professional activities (EPAs) are units of concrete daily clinical tasks that trainee physicians should be able to handle with increasing autonomy during their postgraduate training. EPAs are gaining international recognition as an essential component of competency-based medical training programmes. The process of developing EPAs for a nationwide training programme is complex and requires an in-depth understanding of EPAs as a concept and good knowledge of appropriate development processes. This article provides a detailed description of the methodology and results of a multi-step approach for developing a list of candidate EPAs for Switzerland’s postgraduate training programme in general internal medicine (GIM). METHODS: We took a multi-step approach including a systematic review of international literature, four national focus groups, a national consensus process using a RAND appropriateness method, and a quality check of the selected candidate EPAs using EQual criteria. RESULTS: These steps generated a final list of 247 candidate EPAs in general internal medicine that were submitted for the national consensus process. After two rounds of rating, experts agreed on the appropriateness for general internal medicine postgraduate training of 225 candidate EPAs. Twenty-two were deemed inappropriate, and disagreement persisted only for two EPAs. DISCUSSION: This multi-step programme is one of the few describing in detail the process of developing a list of EPAs and providing evidence of validity at each step. The clinical breadth of our candidate EPAs, together with the detailed description of our methodology, could serve as a useful starting point from which medical education specialists or clinicians could develop or revise applicable lists of EPAs, particularly for postgraduate training programmes in either general internal medicine or family medicine.